The Least Developed countries report 2013 : growth with employment for inclusive and sustainable development. - United Nations (New York : United Nations Publications, 2013)
Annotation UN estimates show that Least Developed Countries (LDCs) population will grow to 1500 million by 2040, and the labour force will almost double. This report aims to raise awareness and galvanise the attention of policy makers to the magnitude of the problem.
Text (electronic book).
Trade
Keywords: Developing countries -- Economic conditions